SYLLABUS IS AN IMPORTANT TOOL IN ORGANISING ESP COURSES: SYLLABUS IS AN IMPORTANT TOOL IN ORGANISING ESP COURSES - Allamuratova, Juldiz (Журнал иностранных языков и лингвистики, 2025)
In today’s high developing modern society, the demand for the competence of English language has reasonably risen in each sphere of community to reach professional development. In this regarding, according to L. Kaidalova’s expert opinion, the teaching and learning support materials complex is the key pedagogical condition of the whole continuous education system functioning [3:257]. That is why, true and full selection of teaching materials contribute to the formation process in the framework of continuous professional training as a key factor of enhancing teaching as well as learning process. In this respect, the content of the syllabus is the important component of the learning and training support materials set which determines the role of each discipline in the course of continuous professional training, its aim, content, the means of academic results assessment [3:257]. The aim of syllabus is to serve as a map of the course for students and explain how to achieve intended results through the course. Ignoring essential components make any teacher to be seen as an unprofessional or absent-minded. To avoid such unfavourable conditions, the course syllabus ought to include all necessary pieces.